Pola adaptasi masyarakat dalam Pengelolaan Hutan Kemasyarakatan (Hkm) di Desa Mirring, Kabupaten Polewali Mandar, Sulawesi Barat - Andi Ridha Yayank Wijayanti; Andi Arafat; Irlan (Fakultas Kehutanan, Universitas Hasanuddin, 2022)
The Mirring Village community is one of the villages that has a dependency on the forest. Before obtaining permission from HKm, the existence of the forest around the village of Mirring was quite critical. Until now, the existence of HKm KTH Buttu Puang is still active and has achievements. So it is important to see how the adaptation pattern of the Mirring village community is with the existence of a Social Forest management permit. The understanding of the adaptation of the Mirring Village community in the development of HKm can be a reference for the parties in the development of HKm in other villages. This research was carried out from January to June 2021. The method used was the method of interviewing groups of forest producers. The results of the study indicate that the community adopts an adaptation pattern that includes ecological adaptation, economic adaptation and social adaptation. In the adaptation pattern studied, in general, the community is considered capable of adapting to the applied HKm management system. Keywords: Adaptation Pattern, Household, HKm, Social Forestry, Community